Percentage of excess body mass index loss and cardiometabolic risk reduction in Peruvian adults undergoing sleeve gastrectomy - Bardelli, María Luisa (2023)
Objective: To assess the association between the percentage of excess body mass index loss (%EBMIL) and cardiometabolic risk reduction in Peruvian adults undergoing laparoscopic sleeve gastrectomy (LSG). Methods: Retrospective cohort study conducted with adult patients who underwent LSG in a bariatric clinic during 2016–2020. The outcome variable was cardiometabolic risk change (expressed in Δ) 1 year after LSG. To that effect, the variables total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein (LDL) cholesterol, very LDL (VLDL) cholesterol, triglycerides, glucose, insulin, and HOMA-IR at baseline and after 12 months were considered. The exposure variable was %EBMIL. Crude and adjusted β coefficients were estimated with linear regression models. Results: Of the 110 patients analyzed, 68.2% were women, and the median patient age was 34.5 years. In the model adjusted for sex, age, and baseline BMI, we noted that each 25% increase in %EBMIL resulted in a decrease in the values for total cholesterol, LDL, triglycerides, and insulin by 10.36 mg/dL (p < 0.001), 7.98 mg/dL (p = 0.001), 13.35 mg/dL (p = 0.033), and 3.63 uU/mL (p = 0.040), respectively. Conclusion: %EBMIL was associated with a decrease in total cholesterol, LDL, triglycerides, and insulin levels, which could suggest a favorable cardiometabolic evolution during the first 12 months following LSG.